+0  
 
0
288
1
avatar

3[g(n)] and g(x)=x^2+5x

Guest Oct 2, 2017

Best Answer 

 #1
avatar+7324 
+1

g(x)  =  x2 + 5x             Plug in  n  for  x .

g(n)  =  n2 + 5n

 

    3[ g(n) ]                    Substitute  n2 + 5n  in for  g(n)  .

=  3[ n2 + 5n ]              Distribute the  3  to each term in parenthesees.

=  3n2 + 15n

 

3[ g(n) ]  =  3n2 + 15n

hectictar  Oct 2, 2017
 #1
avatar+7324 
+1
Best Answer

g(x)  =  x2 + 5x             Plug in  n  for  x .

g(n)  =  n2 + 5n

 

    3[ g(n) ]                    Substitute  n2 + 5n  in for  g(n)  .

=  3[ n2 + 5n ]              Distribute the  3  to each term in parenthesees.

=  3n2 + 15n

 

3[ g(n) ]  =  3n2 + 15n

hectictar  Oct 2, 2017

11 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.